DEVELOPMENT OF A SOFTWARE SYSTEM FOR DATA PROCESSING IN THE FIELD OF REAL ESTATE MARKET ANALYSIS - MISIURKA, PAVLO; KHUDYI, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In a market economy based on the principles of free enterprise, one of the main tasks of subjects of trade and economic relations is the effective allocation of resources. The main task in determining the optimal cost of goods is an analysis that is able to identify patterns and trends in the development of economic processes, establish and evaluate the main factors that positively or negatively affect efficiency indicators. The paper describes the development of a software system for fast and high-quality data processing in the real estate market. The goals of the system’s functioning are formulated. A software system for analyzing the real estate market has been implemented, which fully meets expectations and is partially able to satisfy the needs of real estate market participants who are engaged in its analysis. Real estate market analysis is based on preliminary data collection and processing, monitoring, research and forecasting of market development, therefore, among the problems of its implementation are: • lack of official statistical data, the collection of which is not regulated by anyone, not centralized by anyone, not published anywhere; • lack of analytical centers staffed with highly qualified professionals in various fields; • high dynamism of the real estate market, which can affect the relevance of the collected data. As a result a software system for analyzing the real estate market was implemented, capable of meeting the needs of real estate market participants who are engaged in its analysis. The object of research is the process of identifying patterns and trends in the development of economic processes, establishing and evaluating the main factors that positively or negatively affect resource efficiency indicators. The subject of the study is the features and signs of the influence of trends in the development of economic processes in the real estate market on pricing indicators.